La biomasa y el turismo recreativo en la granja integral de La Universidad Técnica de Babahoyo - Reyes Indio, Xiomara Noemi (2022)
The current research project seeks to identify the components of Biomass to evaluate the use and benefit it provides to Recreational Tourism in the Integral Farm installed in the Faculty of Agricultural Sciences of the Technical University of Babahoyo in order to take advantage of said resource to contribute with environment. At present, many are unaware of what Biomass is, how to obtain it and the benefits it generates, making it a key factor for this project, providing true and reliable information through the documented research method. In this project, research methodologies such as the inductive method are applied, where the collection, experimentation and analysis of the information collected during the research process for the study of Biomass is obtained. The Technical University of Babahoyo has the necessary implements to obtain Biomass and the Integral Farm is a potential innovation that can become a tourist attraction, it is considered that it is of great importance to create alliances with strategic organizations that contribute to the development of Recreational Tourism to generate economic income.